THE IMPACT OF TEMPERATURE ON OPERATOR FATIGUE IN THE DYEING MILLS OF XYZ COMPANY IN BANDUNG - Vicky Avinas; M. Rifqi Ruhyat Hidayat; Muhammad Azdan Akbar; Annisa Maharani Suyono, S.T., M.M (International Journal of Economic Integration and Regional Competitiveness, 2024)
This study aims to investigate the impact of temperature on the fatigue level of operators in Dyeing Mills within the XYZ company environment in Bandung. The research method used is quantitative, employing a simple linear regression approach. The research sample consists of permanent employees in the production department, selected by purposive sampling. Data is collected by the measurement of ambient temperature at the workplace and the completion of the IFRC Japan questionnaire that measures the level of work fatigue. Data analysis indicates a significant correlation between ambient temperature and operator fatigue levels. The results indicate that employees working in higher temperature conditions tend to experience higher levels of fatigue. The implication of this research is the importance for companies to pay attention to the working environment conditions, particularly ambient temperature, as a factor that might affect the well-being and productivity of employees. This finding contributes to the understanding of the influence of the work environment on employee well-being, and provides a basis for companies to take necessary steps to reduce work fatigue and enhance productivity.